A STATISTICAL STUDY OF THE CONTRIBUTION OF SMES IN ALGERIAN ECONOMIC DEVELOPMENT A CASE STUDY OF THE PERIOD 2012-2021 - SAIDAT, Nedjmi; ATAOUAT, Selma; BENCHOUIHA, Bachir (The journal of contemporary issues in business and government, 2024)
This study aims to quantify the contribution of Small and Medium sized Enterprises (SMEs) to socio-economic development through the analysis of its contribution to Employment, Gross Domestic Product (GDP), Added Value outside of Hydrocarbon and Foreign Trade. A statistical study was conducted on the evolution of these indicators during the period between 2012 and 2021 to highlight the importance of SMEs which recorded a continuous evolvement in the creation of jobs and wealth demonstrated by the share of added value. Despite this modest contribution, the findings showed that the role of SMEs in exports remains insufficient, which belays the dependence on rentier economy.